COMMUNITY PERCEPTIONS OF SERVICE QUALITY AT THE SADIA VILLAGE OFFICE, BIMA CITY - Subhekti, Erika Fajar; Subhekti, Erick Fajar; Nadia, Fiona Niska Dinda; Tamaya, Nyi Dela (Universitas Airlangga, 2025)
Public services at the urban village level play a strategic role in reflecting the presence of the state and influencing the level of community satisfaction. However, in practice, public services still face challenges in terms of responsiveness, clarity of procedures, and apparatus attitudes. This study aims to explore community perceptions of service quality at the Sadia Village Office, Bima City. The approach used was descriptive qualitative, with data collection through in-depth interviews, direct observation, and documentation. Informants were selected purposively based on direct experience of receiving village services. The results showed that service quality was influenced by several main factors, namely the friendly and communicative attitude of officers, clarity of procedures, limited service facilities, and service speed. These findings were analyzed based on the five dimensions of SERVQUAL, and showed that non-technical aspects such as empathy and interpersonal communication play an important role in shaping community satisfaction. The conclusion of this study is that although services in Kelurahan Sadia are generally considered quite good, improvements in technical aspects and provision of facilities are still needed to improve the overall quality of public services